2017
DOI: 10.1186/s13148-017-0404-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of interferon signaling-related microRNAs in occult hepatitis B virus infection

Abstract: BackgroundOccult hepatitis B virus infection (OBI) is an important risk factor of liver cirrhosis and hepatocellular carcinoma. Type 1 interferon (IFN) signaling-related miRNAs were significantly associated with hepatitis B virus (HBV) infection. However, the characteristics of serum IFN signaling-related miRNAs in OBI remain unclear. Therefore, this study aimed to analyze the expression levels of serum IFN signaling-related miRNAs in OBI and to evaluate their potential values for OBI diagnosis.MethodsTwenty s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
14
1
Order By: Relevance
“…In patients with OBI, it has been found that the substitution of G-to-A at position 458 of the surface gene interferes with the splicing of S gene mRNA and was associated with a lack of HBsAg expression and low replication of HBV DNA. 29 Some early data suggested that micro-RNAs may play a role in OBI, as decreased serum miR-122 level and increased miR-130a level were found significantly associated with OBI 30 ; combing miR-122 and miR-130a may potentially serve as a surrogate algorithm to diagnose. Another pilot study of a 4-serum miRNA signature, which includes let-7c, miR-23b, miR-122, and miR-150, shows a high level of accuracy in discriminating OBI cases from the non-infected controls with an accuracy of more than 99%.…”
Section: Virologic and Molecular Mechanisms Of Obi Virologic Mechanismsmentioning
confidence: 99%
“…In patients with OBI, it has been found that the substitution of G-to-A at position 458 of the surface gene interferes with the splicing of S gene mRNA and was associated with a lack of HBsAg expression and low replication of HBV DNA. 29 Some early data suggested that micro-RNAs may play a role in OBI, as decreased serum miR-122 level and increased miR-130a level were found significantly associated with OBI 30 ; combing miR-122 and miR-130a may potentially serve as a surrogate algorithm to diagnose. Another pilot study of a 4-serum miRNA signature, which includes let-7c, miR-23b, miR-122, and miR-150, shows a high level of accuracy in discriminating OBI cases from the non-infected controls with an accuracy of more than 99%.…”
Section: Virologic and Molecular Mechanisms Of Obi Virologic Mechanismsmentioning
confidence: 99%
“…Although research regarding the expression levels and associated functions of miRNA-122 in HCC and other liver diseases have been widely carried out (15,28), the reports are diffuse and contradictory. For example, miRNA-122 acted as a cancer suppressor gene and was downregulated in HCC tissues and cells compared with the adjacent normal tissues and normal cell lines (15,29), which was in line with the results of TCGA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to HCs, miR‐122 was significantly downregulated, while miR‐130a was significantly upregulated in OBI. Moreover, miR‐122 and miR‐130a could also discriminate OBI from HCs, ASC, and CHB (≥0.87 of AUC) . However, the differential expression of these miRNAs was not found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…But it could reduce HBV pregenomic RNA encapsidation and capsid assembly . However, little information is available about miRNAs engaged in OBI and the regulatory mechanisms of these miRNAs remain largely unknown …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation